Menopause A Multidisciplinary Look at - Francisco Rodriguez-Landa, Juan; Cueto-Escobedo, Jonathan (IntechOpen, 2017)
Menopause is a natural state of development in women, but it is also a period of vulnerability to the development of several disorders, such as vasomotor symptoms, hot flashes, vaginal dryness, osteoporosis, cognitive deterioration, depression, and anxiety. Factors as diverse as culture, diet, exercise, maternity, age, and genetics can influence the severity of symptoms that are experienced during menopause and can modify the response to diverse therapies. Studying menopause from a multidisciplinary perspective will help elucidate the different factors that affect health during this specific stage of a woman's life. This book presents several aspects of menopause, including its evolutionary origins, novel nonhormonal therapies, and the neurobiology of related disorders.